Possible electrochemical corrosion of rails on a railway track electrified with direct current - Józef Dąbrowski (Przegląd Komunikacyjny)
Abstract: The article describes the construction of a railway line electrified with direct current. Attention is paid to the isolation of the elements leading to the traction current in the supply and return network, and to the difference in significance of these insulations. The reasons for the occurrence of stray currents and their nature in any cross-section of the track on the trail are given. The necessary conditions for the disclosure of electrochemical processes on the rails of the track tracks were shown. It has been shown that the galvanization processes occur locally on the trail - the application of soil electrolyte ions on the surface of the rails and electrochemical corrosion - the loss of the rails material. During the movement of electrified trains on the route, moisture is necessary and the contact of the rails with the poorly drained support of the foot or with the ballast - track ballast. Keywords: Electrified railway route; Stray currents; Electrochemical corrosion